Adequate tacrolimus exposure modulates the impact of HLA class II molecular mismatch: a validation study in an American cohort. Issue 1 (11th October 2020) - Davis, Scott; Wiebe, Christopher; Campbell, Kristen; Anobile, Cheri; Aubrey, Michael; Stites, Erik; Grafals, Monica; Pomfret, Elizabeth; Nickerson, Peter; Cooper, James E.
Abstract : Clinicians have few tools to predict the risk of alloimmune injury that would guide immunosuppression management in renal transplant patients. We evaluated human leukocyte antigen (HLA)‐DR/DQ molecular mismatch to predict de novo donor‐specific antibodies (DSAs) during the first year of transplant and explored how differences in tacrolimus exposure may modulate this risk. HLA‐DR and ‐DQ eplet mismatches were determined between 444 donor‐recipient pairs in Denver, Colorado between 2007 and 2013. Previously defined mismatch thresholds stratified recipients into low‐ (N = 119), intermediate‐ (N = 153), and high‐ (N = 172) risk categories. The area under the curve for DSA at 1 year was 0.84 and 0.82 for HLA‐DR and HLA‐DQ eplet mismatches, respectively. Compared to low‐risk patients, there was a graded increase in risk of DR/DQ DSA in intermediate (HR 15.39, 95% CI 2.01‐118.09, p  = .009) and high‐risk (HR 23.81, 95% CI 3.17‐178.66, p  = 0.002) categories. Intermediate‐ and high‐risk patients with a mean tacrolimus <6 ng/ml versus >8 ng/ml had increased risk of DR/DQ DSA at 1 year (HR 2.34, 95% CI 1.05‐5.22, p  = .04). HLA molecular mismatch represents a reproducible, objective, and clinically relevant tool to stratify patients by alloimmune risk and may help guide personalized immunosuppression management. Abstract : DR/DQ molecular mismatch predicts the development of de novo donor‐specific antibodies after kidney transplantation, with a graded increase in risk for intermediate and high molecular mismatch patients that is modulated by differences in tacrolimus exposure. Jackson and Pinelli's editorial is on page 9.